''قانون بین الاقوام کی بنیادیں عہد اسلامی میں''ایک تحقیقی جائزہ: '' Foundations of International Law in the Islamic era '' (An Exploratory review) - Umair, Hafiz Muhammad; Khokhar, Dr. Mahmood Sultan (Al-Amīr Research Journal for Islamic Studies, 2022)
Human nature has become collectivist. And man's survival is in living together and fulfilling the necessities of life through mutual cooperation. As a result, a system of mutual relation is formed; the state has relation with the other state just as the individual has relations with the individual. If there is no balance and harmony in this relationship, then mutual conflict and tension is natural. In fact, international law has its beginnings from the Islamic era. The Prophet (peace and blessings of Allah be upon him) conveyed the universal message of the Islamic State throughout the world through his foreign Strategy and diplomatic letters. Away from the concept of globalization, the importance of foreign relations has become more important in modern times. Therefore, just as it is necessary for the Islamic state to harmonize with the world conditions and events according to the requirements of the modern era, it is also necessary for the Islamic state to keep its ideological position in mind in all situations. So that the foreign strategy of the Islamic State is established on strong foundations and its principles are formulated in the light of International Law and Sharia. Keywords: International Law, Foreign Policy, Foundations, Islamic era